2016
DOI: 10.1051/parasite/2016072
|View full text |Cite
|
Sign up to set email alerts
|

Triloculotrema euzetin. sp. (Monogenea, Monocotylidae) from the nasal tissues of the blackspotted smooth-houndMustelus punctulatus(Carcharhiniformes, Triakidae) from off Tunisia

Abstract: Triloculotrema euzeti n. sp. (Monogenea, Monocotylidae, Merizocotylinae) is described from the nasal tissues of the blackspotted smooth-hound Mustelus punctulatus collected from the coastal marine waters off Tunisia. The new parasite species is distinguished from the other two species of the genus, T. japanicae Kearn, 1993 and T. chisholmae Justine, 2009, by the morphology of the sclerotised male copulatory organ which has longitudinal ridges. The species is also characterised by its oötype with short descendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
“…Recent studies have shown that the biodiversity of monogeneans of marine fish in the southern part of the Mediterranean is far from being completely known (Chaabane et al, 2015(Chaabane et al, , 2016a(Chaabane et al, , b, 2017Chaari et al, 2016;Kheddam et al, 2016;Boudaya & Neifar, 2016;Ayadi et al, 2017). In the course of a parasitological study of monogeneans of sparid fishes off the Algerian coast, we collected representatives of an undescribed species of Microcotyle on the gills of Pagrus caeruleostictus.…”
Section: Microcotyle Visamentioning
confidence: 99%
“…This paper is a part of an ongoing effort to characterise the parasite biodiversity of fish of the southern shores of the Mediterranean Sea (Ayadi et al 2017;Boudaya and Neifar 2016;Bouguerche et al 2019;Chaabane et al 2015Chaabane et al , 2016aChaabane et al , b, 2017Chaari et al 2016;Kheddam et al 2016;Kouider El Ouahed-Amine 1998).…”
Section: Introductionmentioning
confidence: 99%
“…This paper is part of a series on monogeneans of fishes of the South shore of the Mediterranean Sea ( i.e. , Ayadi et al, 2017 ; Azizi et al, 2021 ; Boudaya & Neifar, 2016 ; Bouguerche et al, 2019a , 2019b , 2019c ; Bouguerche, Justine & Tazerouti, 2020 ; Bouguerche et al, 2020 , 2021 ; Chaabane, Neifar & Justine, 2015 ; Chaabane et al, 2016a , 2016b ; Chaabane, Neifar & Justine, 2017 ; Kheddam, Justine & Tazerouti, 2016 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%